CRUISING FOR BURGERS. - Mattingly, George (Spirit That Moves Us: The Actualist Anthology, 1977)
The article presents the poem "Cruising for Burgers," by George Mattingly. First Line: The radio exploded without a sound. Then the air was filled; Last Line: this many times, then he flew away.